Synthesis, Antimicrobial and Antioxidant Activity of Pyrazole Based Sulfonamide Derivatives - Badgujar, Jagdish R. (Indian J Microbiol, 2017)
A series of new sulfonamides have been synthesized from Ampyrone with different benzene sulfonyl chlorides to yield the N-1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl) benzenesulfonamides (4a–e). All synthesized compounds were characterized on the basis of FTIR, (1)H NMR, and (13)C NMR, and also by the aid of mass spectral data. Further, all synthesized compounds have studied for their in vitro antimicrobial activities against selected bacterial as well as fungal strains by the agar well diffusion method. Free radical scavenging activity has been investigated by using DPPH method. Among all the synthesized compounds, 4b, 4d, and 4e exhibited significant antimicrobial and antioxidant activities. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12088-017-0689-6) contains supplementary material, which is available to authorized users.